The becoming of the complex fears among young people: reflection through the prism of the genotype of the domestic culture - Sergej A. Kravchenko; Daria A. Svirskaya (Социологическая наука и социальная практика)
The article examines the process of the development and complication of fears, starting with the transition from the traditional society to the “risk society” and the “world risk society” and further to the modern society, the essential features of which, according to the anthropo-sociocultural approach of N. I. Lapin, are “synergistic complexities”. They represent realities as the result of a nonlinear process of their formation in the context of the past, present and future. Their immanent essence is manifested in self-development, self-organization and hybridization of nature, society, technology that is expressed in the emergent effects of instability, inequality, dynamic chaos, which produce fears for people about the uncertainties of the present and future. Specifically, two types of the synergistic complexities are considered, which are the determinants of the “culture of fear” (U. Beck) and the formation of a specific fear market in which staged fears of the complex type dominate and the means of their “treatment” are sold. However, the content of fears is determined not only by global trends in the transformation of the universe, but also by local national factors and, above all, by the genotype of the country’s culture. In this regard, foreign pragmatic approaches to minimizing fears are critically analyzed, which are contrasted with the research of the domestic scientists offering culturally determined means of overcoming them. In the conclusion, the authors substantiate the contours of the concept of a strategy for the reflexive treatment of fears, aimed at counteracting the penetration of staged fears into the consciousness of Russian youth.